Seeds for a Mature Compositional Style: An Analysis of Melody, Musical Layers, and Signals in Claude Vivier’s Chants - Harman, Brian (Intersections, 2013)
Claude Vivier’s Chants is considered by many to be his first significant musical composition, yet very little exploration has been undertaken to determine what techniques and ideas flow from this work into his mature musical style. This article provides an in-depth analysis of Chants’ pitch organization and the influence of the principal melody on the work as a whole, followed by an analysis of the manipulation of musical layers and the use of processes as signals for formal change in the work. These qualities bear strong similarities to Vivier’s later works, demonstrating that Chants was pivotal in his development as a composer.